Dynamic Current–Voltage Analysis of Oxygen Vacancy Mobility in Praseodymium‐Doped Ceria over Wide Temperature Limits. (23rd January 2020) - Kalaev, Dmitri; Defferriere, Thomas; Nicollet, Clement; Kadosh, Tamar; Tuller, Harry L.
Abstract : Solid‐state mixed ionic–electronic conductors (MIECs) in which ionic transport is commonly accompanied by predominant electronic conductivity underpin key technologies and require universal characterization methods for monitoring transport at the nanoscale, at both high and near ambient temperatures, the latter being especially challenging. In this study, a novel dynamic current–voltage analysis technique is utilized to decouple ionic and electronic transport properties from each other. The versatility of the method is demonstrated by enabling measurement of the oxygen vacancy mobility in Pr0.1 Ce0.9 O2− δ thin films, across an unusually wide temperature range, from 35 to 500 °C. Despite the presence of predominant electronic conduction, the oxygen vacancy mobility in Pr0.1 Ce0.9 O2− δ is measured, being 6.8 × 10 −6 cm 2 V −1 s −1 at 500 °C, decreasing by seven orders of magnitude down to 35 °C, and following a single thermal activation energy of 0.82 ± 0.02 eV. A comparison with previous reports on oxygen vacancy transport and with the one derived in this study from impedance spectroscopy, interpreted with the Jamnik–Maier model, further confirms the dynamic current–voltage analysis results. This method can more generally be applied to other types of MIECs, thereby enabling deeper insights into mobile ionic defect transport and accompanying thermodynamic properties. Abstract : A novel dynamic current–voltage analysis technique is utilized to measure oxygen vacancy mobility in Pr0.1 Ce0.9 O2− δ thin films, found to be 6.8 × 10 −6 cm 2 V −1 s −1 at 500 °C, decreasing by factor of 10 7 at 35 °C and following an activation energy of 0.82 eV. Such measurements are of special interest for nanoelectronic devices that depend on ion transport for operation.